Funeral customs of Warsaw Evangelicals in the 19th century - Stegner, Tadeusz (Requiem, 2025)
At the end of the 19th century, Evangelicals constituted 4.6% of the population of Warsaw. They included representatives of various social groups, from manufacturers, merchants, intellectuals to workers, and most of them used Polish on a daily basis. Since the end of the 18th century, there have been two cemeteries in the capital: the Evangelical-Augsburg one and the Evangelical-Reformed one. The rituals associated with funerals in Warsaw’s evangelical communities were not very different from those in force among the middle class and other Christians. The differences resulted from religious principles, e.g. the lack of last rites or belief in purgatory, hence no candles were placed on the graves. There were special regulations established by congregations regarding funeral arrangements and fees for religious services. In addition to funerals, mourning celebrations were organized in honor of famous people, e.g. Prince Józef Poniatowski or the Emperor of Russia and King of the Kingdom of Poland, Alexander I.